Indirectly Recognized HLA-C Mismatches and Their Potential Role in Transplant Outcome - Thus, Kirsten A.; Te Boome, Liane; Kuball, Jürgen; Spierings, Eric (Frontiers in Immunology, 2014)
HLA-C mismatches are clearly associated to alloreactivity after hematopoietic stem-cell transplantation; in a number of large cohorts, HLA-C mismatches are correlated to an increased risk of acute graft-versus-host disease (GVHD) or even impaired survival. While for HLA-A and -B, both antigenic as well as allelic mismatches are associated with an increased risk of acute GVHD, such an increased risk is only observed for antigenic HLA-C mismatches and not for allelic mismatches. These observations raise the question what sets HLA-C apart from HLA-A and -B. The difference may well be related to the reduced levels of cell-surface expression of HLA-C as compared to HLA-A and -B, possibly due to, among other factors, a limited peptide-binding capacity. This limited peptide-binding capacity may retain HLA-C in the ER and enhance degradation of the HLA-C protein. Once degraded, HLA-C-derived peptides can be presented to the immune system via other HLA alleles and are thus available for indirect recognition. Indeed, such HLA-C-derived peptides have previously been eluted from other HLA alleles. We have recently developed an approach to predict indirect recognition of HLA molecules, by establishing the numbers of predicted indirectly recognizable HLA epitopes (PIRCHES). The number of PIRCHES presented on HLA class I and II (PIRCHE-I and -II, respectively), are highly correlated to clinical measures of alloreactivity, such as acute GVHD. In the present “Hypothesis & Theory,” we reviewed the current knowledge on HLA-C mismatches and alloreactivity. Moreover, we speculate about the role of direct and indirect recognition of HLA-C and the consequences for donor selection in HLA-C mismatched stem-cell transplantation.